Peranan Ketua Pengurus dan Manajer Dalam Penyusunan dan Penerapan Laporan Keuangan Berbasis SAK ETAP Pada Koperasi di Kota Palembang - Syahputera, Riza; Rianty N, Martha (Jurusan Akuntansi Politeknik Negeri Padang, 2019)
This study aims to determine the effect of the role of the Chairperson and Cooperative Manager in the preparation and application of Financial Statements based on SAK ETAP in cooperatives in the city of Palembang. This research is a quantitative study using data obtained from questionnaires and measured using a Likert scale. The sampling technique used is purposive sampling. The sample used in this study was the Chairperson of the cooperative and the manager of the cooperative in the city of Palembang. The cooperatives studied were 203 cooperatives. The data analysis technique used is multiple linear regression test. The results showed that the role of cooperative leaders and managers had a significant positive effect on the preparation and application of SAK ETAP-based financial statements.